Diskripsi Mengharapkan Segala Sesuatu Sebagaian Unsur Karakter Hamba Tuhan Sebagai Implementasi Kasih Dari Perspektif Korintus 13 : 7 - Wiji Suko Widodo; Aji Suseno (Pusat Studi Pentakosta Indonesia, 2025)
The influence of hedonistic Greek culture in Corinth had shaped the congregation's lifestyle, emphasising self-interest, competition, and division, thereby eroding Christian love in their faith and church fellowship. This situation caused concern for the Apostle Paul because the Corinthian congregation, despite being rich in spiritual gifts, had lost love as the foundation of relationships, ministry, and the unity of the body of Christ. It is in this context that the phrase ‘hoping all things’ in 1 Corinthians 13:7 becomes a theological affirmation that true love originates from Christ and leads believers to live in active, patient, and unifying hope. The purpose of this article is to examine the meaning of ‘hoping all things’ as an element of the character of God's servants in the implementation of Christ's love based on the perspective of 1 Corinthians 13:7. This study uses a descriptive qualitative method through an exegetical study of the biblical text and an analysis of relevant theological literature and scientific journals. The results of the study show that hope in love is not passive, but rather oriented towards Christ as the centre of faith, example of life, and source of unity. This hope encourages servants of God to continue to prioritise love in the midst of conflict, suffering, and differences in the church and society. Thus, expecting everything in Christ's love becomes an important foundation for the formation of the character of servants of God who are humble, have integrity, and are committed to maintaining the unity of the body of Christ.AbstrakPengaruh budaya Yunani yang hedonistik di Korintus telah membentuk pola hidup jemaat yang menekankan kepentingan diri, persaingan, dan perpecahan sehingga nilai kasih Kristiani semakin tergerus dalam kehidupan iman dan persekutuan gerejawi. Kondisi tersebut menimbulkan keprihatinan rasul Paulus karena jemaat Korintus, meskipun kaya karunia rohani, kehilangan kasih sebagai dasar relasi, pelayanan, dan kesatuan tubuh Kristus. Dalam konteks inilah ungkapan “mengharapkan segala sesuatu” dalam 1 Korintus 13:7 menjadi penegasan teologis bahwa kasih sejati bersumber dari Kristus dan menuntun orang percaya untuk hidup dalam pengharapan yang aktif, sabar, dan mempersatukan. Tujuan penulisan artikel ini adalah mengkaji makna “mengharapkan segala sesuatu” sebagai unsur karakter hamba Tuhan dalam implementasi kasih Kristus berdasarkan perspektif 1 Korintus 13:7. Penelitian ini menggunakan metode kualitatif deskriptif melalui kajian eksegetis teks Alkitab serta analisis literatur teologis dan jurnal ilmiah yang relevan. Hasil kajian menunjukkan bahwa pengharapan dalam kasih tidak bersifat pasif, melainkan berorientasi pada Kristus sebagai pusat iman, teladan hidup, dan sumber kesatuan. Pengharapan tersebut mendorong hamba Tuhan untuk tetap mengedepankan kasih di tengah konflik, penderitaan, dan perbedaan dalam gereja maupun masyarakat. Dengan demikian, mengharapkan segala sesuatu dalam kasih Kristus menjadi fondasi penting bagi pembentukan karakter hamba Tuhan yang rendah hati, berintegritas, dan berkomitmen menjaga kesatuan tubuh Kristus.